PENGARUH LEVERAGE, PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Manurung, Irma Maria Octa Moravia; Prima, Argo Putra (SCIENTIA JOURNAL, 2019)
This research aims to know the influence of leverage, profitability and firm size against firm value either partially or simultaneously. The researcher wants to do research in manufacturing companies sub-sector food and beverage listed in Indonesia Stock Exchange period 2013-2017 using purposive sampling method. The dependent variable in this study is firm value and the independent variables are leverage, profitability and firm size. This method of analysis of this study uses multiple linear regression test using SPSS version 22. The results of this study showed that leverage has significant effect partially with t-count > t-table or 3,029 > 1,68830 with significance value 0,005 < 0,05. Profitability has no significant effect partially with t count < t tabel or 0,020 < 1,68830 with significance value 0,984 > 0,05. Firm size has no significant effect partially with t count < t table or 0,480 < 1,68830 with significance value 0,634 > 0,05. Leverage, profitability, and firm size have significant effect simultaneously against firm value with F count > F table or 4,811 > 2,87 with significance value 0,006 < 0,05. Adjusted R Square showed 22,7% or 0,227 while the rest 77,3% is explained by others variables that not examined.